THE MULTIFACETED ROLE OF BILINGUALISM IN MODERN SOCIETY: COGNITIVE, CULTURAL, AND ECONOMIC PERSPECTIVES: THE MULTIFACETED ROLE OF BILINGUALISM IN MODERN SOCIETY: COGNITIVE, CULTURAL, AND ECONOMIC PERSPECTIVES - Muratbaeva, Shinar (Журнал иностранных языков и лингвистики, 2025)
In an increasingly interconnected world, bilingualism has evolved from a mere advantage to a necessity. As cultures and economies grow interdependent, the ability to speak multiple languages offers cognitive, social, and economic benefits. In teaching English the students should be taught not only to have knowledge on particular subjects as grammar, speaking, writing, listening etc. but they also should have been introduced with educational-upbringing materials on, for instance, culture, moral, customs and rituals of every-day-use of the people living in English speaking countries [1; 56]. Research by Bialystok (2001) highlights its impact on memory and executive function, while its broader societal advantages from intercultural harmony to global trade make it a cornerstone of modern progress. Beyond individual advantages, bilingualism plays a key role in fostering intercultural understanding, economic growth, and political inclusivity.